2011
DOI: 10.1530/eje-11-0261
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum TSH concentration within the normal range and adiposity

Abstract: Background: Overt hypothyroidism is clearly related to body weight gain and greater adiposity, but the range of hormonal change in serum TSH concentration associated with weight gain remains a focus of debate. Aim: The aim of this review was to assess studies that evaluated the relationship between anthropometric measures and serum TSH concentration in euthyroid subjects. Methods: Studies held on the Ovid MEDLINE database were searched and original articles published from 2000 to 2010 were included. The litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 44 publications
(60 reference statements)
3
35
1
2
Order By: Relevance
“…Indeed, a great deal of research has been conducted to elucidate the association between thyroid function and obesity or BMI. However, data conflict with regard to whether mild hypothyroidism, subclinical hypothyroidism, or both are associated with obesity (18). Although the studies showing positive relationships mostly involved morbidly obese subjects (19,20,21,22,23), we were able to demonstrate a significant relationship between thyroid function and regional fat accumulation in nonobese, euthyroid men, in spite of a relatively small sample.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, a great deal of research has been conducted to elucidate the association between thyroid function and obesity or BMI. However, data conflict with regard to whether mild hypothyroidism, subclinical hypothyroidism, or both are associated with obesity (18). Although the studies showing positive relationships mostly involved morbidly obese subjects (19,20,21,22,23), we were able to demonstrate a significant relationship between thyroid function and regional fat accumulation in nonobese, euthyroid men, in spite of a relatively small sample.…”
Section: Discussioncontrasting
confidence: 56%
“…A recent review of 29 studies assessed the relationship between serum TSH and BMI in euthyroid subjects (58). Eighteen of these studies showed a positive correlation between the measures of adiposity and serum TSH.…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 99%
“…adipose and muscle tissue. Apart from overt dysfunction, changes in body weight also correlate with serum TSH concentrations even within the normal range [55], this cross-sectional, population-based study (included patients older than 40 years of age) describes a positive association of subclinical hypothyroidism with obesity. A study by Ittermann et al [56] found a positive correlation of TH status and BMI in adolescence, which was stronger in individuals exposed to smoke (either actively or passively).…”
Section: Human Datamentioning
confidence: 99%